Victorian Faddishness: The Dolly Varden from Dickens to Patience. (10th April 2021) - Mitchell, Rebecca N
Abstract: This article addresses the origins and nature of the fad through a case study of the 'Dolly Varden' dress. The gown originated in the 1770s as a 'polonaise' among continental aristocracy, and experienced a minor revival in the 1840s when Dolly Varden, a character in Charles Dickens's novel Barnaby Rudge (1841) was depicted wearing it. But it did not become a fad until the 1870s, after a Dickens-owned painting of the character was sold and the gown re-entered the public eye. Having shed its historical or literary connections, the gown was revived again in Gilbert and Sullivan's comic opera Patience (1881), a well-known send-up of Aesthetic foibles. Often overlooked is the fact that dairy maid Patience – who figures in the opera as a counterpoint to the lovesick maidens wearing high Aesthetic garb – wears a Dolly Varden gown, as faddish as any Aesthetic gown, only slightly outdated. The Aesthetic afterlife of the dress demonstrates the mutability of Victorian fads and the gleeful ignorance of antecedents that typifies fad culture. Facilitated by the material and commercial innovations of the period and fuelled by an insistent presentism, fads are – this article argues – a truly Victorian phenomenon.